The influence of cervical lymph node number of neck dissection on the prognosis of the early oral cancer patients - Chieh-Yuan Cheng; Fang-Ju Sun; Chung-Ji Liu (Elsevier, 2020)
Background/purpose: The status of neck lymph nodes (LNs) plays an important role in survival of oral cavity cancer. Early stage oral cancer patients are still at a risk for locoregional metastasis. We aimed to determine the number of LNs that needs to be retrieved for adequate diagnosis and treatment of the neck tumor. Materials and methods: We conducted a retrospective study of 126 oral cavity cancer patients who underwent wide excision and 3 types of neck dissection at MacKay Memorial Hospital, Taiwan. Data from the operative and pathology reports were collected and analyzed. The significant difference was defined as p < 0.05 by SPSS 21.0 and Prizm 5 software. Results: There was a significant difference between the total retrieved LNs and tumor differentiation and nerve invasion on multivariate analysis. Receiveroperating characteristic (ROC) curve showed significant difference in the total number of neck LNs between the survival and expired groups. The cut-off point was 36.5 nodes. However, there was no difference in survival between supraomohyoid and modified radical neck dissection. Conclusion: Retrieval of adequate LNs can improve oral cancer survival rates. If total number of neck nodes examined is <37 with poor differentiation and/or nerve invasion, early oral cancer patients with neck dissection have a lower survival rate and are candidates for adjuvant therapy.